Gelatin-Based Edible Coating Combined with Mentha pulegium Essential Oil as Bioactive Packaging for Strawberries - Mohamed Aitboulahsen; Said Zantar; Amin Laglaoui; Hicham Chairi; Abdelhay Arakrak; Mohammed Bakkali; Mounir Hassani Zerrouk (Journal of Food Quality)
The effect of gelatin-based edible coating incorporated with Mentha pulegium essential oil (MEO) on physicochemical (pH, titratable acidity (TA), weight loss, total soluble solids (TSS), and total phenolic content (TPC)), microbiological (total aerobic mesophilic flora (TAMF) and yeasts and moulds (YM)), and sensorial (color and firmness) characteristics of strawberries stored under refrigeration was studied. Strawberries were coated with gelatin alone (4%) and/or gelatin combined with two concentrations (0.5 and 1%) of MEO and stored at 4°C for 13 days. Gelatin coating and MEO combination significantly inhibited total flora and moulds and yeasts with comparison to control (uncoated strawberries) and had better hygienic quality at the end of storage. The effect was MEO concentration dependent. Our results also showed that the bioactive coating used in this investigation slowed down changes in pH, TA, weight loss, TSS, firmness, TPC, and color of strawberries. Gelatin coating incorporated with MEO at 1% protected at least 60% of strawberries from deterioration after 13 days of storage and could be used as bioactive packaging to prolong the shelf life and an alternative of pesticides use.